Career Resilience and Advancement : A Research Note on Women in Indian IT - Murthy, Rupashri N.; Antony, Janis Maria (Prabandhan: Indian Journal of Management, 2025)
Purpose : The representation of women in the Information Technology (IT) industry in India is higher than in other sectors. However, many women leave the industry after five years of employment. Organizations are concerned about the gender gap in leadership positions within this sector. The paper suggested that career resilience (CR) is a strategic method for retaining and advancing women in IT professions. Methodology/Approach : The paper employed an interpretive synthesis approach. Literature from peer-reviewed sources on CR, career development, and career advancement of women professionals was reviewed. Findings : The synthesis of literature highlighted the role of CR in improving women’s continued participation in the industry. The findings suggested building resilience through organizational interventions as a way forward to creating a more gender-equitable workforce. Practical Implications : The strategies presented are practical and feasible for IT organizations to create a more inclusive workspace. These strategies are designed to empower organizations to take meaningful steps for an equitable workforce. Originality : The paper presented a comprehensive approach to sustaining and advancing women in the IT industry in India.